Sala de aula invertida: ensinagem dos sistemas de equações polinomiais do 1º grau no oitavo ano do ensino fundamental - Scolaro, Joelma Kominkiewicz (2020)
This study is linked to the research trend Information, Communication and Interaction Technologies applied to the Teaching of Mathematics and Science and aims to investigate the potentialities of the flipped classroom, associated to the use of Digital Information and Communication Technologies (DICTs) in the process of teaching of 1st degree polynomial equations with students from the eighth year of Elementary School. The guiding question of the study is: how does the flipped classroom technique associated to Digital Information and Communication Technologies (DICTs) can contribute to the teaching process of 1st degree Polynomial Equation Systems at the eighth year of Elementary School? The active methodologies, which involve in practice present and online teaching, triggers the student’s interest to research, and curiosity to the use of technological tools, which has become a form of teaching also known as “hybrid teaching”. Hybrid teaching has a few models of teaching, among them the flipped classroom, a pedagogical model which inverts the traditional learning model. During the research and study term, an educational product was made, in the form of a sequence of activities, structured in thirteen meetings and applin on a class of the eighth year of Elementary School with twenty-four students of a private school in the city of Campos Novos, in Santa Catarina state, Brazil. The flipped classroom active methodology educational product was structured in three moments: pre-class, during class and post-class, in which introductory elements of systems of equations with two variables were approached, as well as with the formation of groups for the development of activities during class. Methodologically, the research proposed on this study classifies as qualitative approach; in terms of goals as explanatory; and as for the technical procedures, as participant. As data collection instrument, the researcher’s journal was used, as well as reports from Kahoot, an interactive notebook, feedback from Google Classroom, including a portfolio made by the student’s groups in the development of the sequence, along with the development of the proposed activities and the closing seminar. The results found demonstrate that the activities sequence, organized as in a flipped classroom, has favoured the placement of DICTs and the group project making the participants active in the teaching process of the systems of 1st degree polynomial equations with two variables. Still, the data collected during the application of the activities sequence has presented evidence of learning and knowledge acquisition by the students, thus reaching the proposed objectives. Finally, the present dissertation is made-up by an educational product in the form of a sequence of activities developed as aiming to provide didactical-methodological resources to Mathematics teachers of Elementary School II, available in <http://educapes.capes.gov.br/handle/capes/568910>.